PENGARUH KERAGAMAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI UD. DEAN DESA IDALA JAYA KECAMATAN MANIAMOLO - Waoma, Amos Febrianto (PARETO : Jurnal Riset Bisnis dan Manajemen, 2024)
This research aims to determine the influence of product diversity and price on purchasing decisions at UD. Dean. The type of research used in this research is quantitative research that is associative in nature. The sampling technique used is non-probability sampling with an incidental sampling technique. The sample used in this research was UD consumers. Dean numbered 35 people. The data collection technique used in this research is the questionnaire technique. The analytical method that will be used to test the hypothesis used in this research is multiple linear regression analysis. The results of this research show that partially and simultaneously, product diversity and price variables have a positive and significant effect on purchasing decisions at UD. Dean of Idala Jaya Village. The conclusion in this research is that the product diversity variable (X1) and the price variable (X2) influence purchasing decisions (Y) at UD. Dean. The suggestion in this research is to ensure that consumers continue to make purchases, then UD. Dean should provide several inventories of various product sizes so that consumers can have products according to the size they buy and to maintain customer loyalty, it is better for UD. Dean provides prices that are lower than competitors' prices and the prices are adjusted to the quality of the product, so that consumers continue to make purchases.